The search for genes contributing to endometriosis risk. - Montgomery, G; Nyholt, DR; Zhao, Z; Treloar, SA; Painter, J; Missmer, SA; Kennedy, S; Zondervan, K (2008)
BACKGROUND: Genetic variation contributes to the risk of developing endometriosis. This review summarizes gene mapping studies in endometriosis and the prospects of finding gene pathways contributing to disease using the latest genome-wide strategies. METHODS: To identify candidate-gene association studies of endometriosis, a systematic literature search was conducted in PubMed of publications up to 1 April 2008, using the search terms 'endometriosis' plus 'allele' or 'polymorphism' or 'gene'. Papers included were those with information on both case and control selection, showed allelic and/or genotypic results for named germ-line polymorphisms and were published in the English language. RESULTS: Genetic variants in 76 genes have been examined for association, but none shows convincing evidence of replication in multiple studies. There is evidence for genetic linkage to chromosomes 7 and 10, but the genes (or variants) in these regions contributing to disease risk have yet to be identified. Genome-wide association is a powerful method that has been successful in locating genetic variants contributing to a range of common diseases. Several groups are planning these studies in endometriosis. For this to be successful, the endometriosis research community must work together to genotype sufficient cases, using clearly defined disease classifications, and conduct the necessary replication studies in several thousands of cases and controls. CONCLUSIONS: Genes with convincing evidence for association with endometriosis are likely to be identified in large genome-wide studies. This will provide a starting point for functional and biological studies to develop better diagnosis and treatment for this debilitating disease.